Cinnamomum burmannii improves insulin serum level in the normal obese subjects : preliminary study - Hari Hendarto; Flori R Sari; Chris Adhyanto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Obesity is characterized with excessive accumulation of the body fat which occurs whenthe energy intake exceeds the expenditure. It is routinely associated with insulin resistanceand hyperinsulinemia. Additionally, suppressing insulin level protects female mice fromweight gaining. Cinnamon [Cinnamomum burmannii (Ness) Bl. Cortex] suppresseshyperinsulinemia condition in the type 2 diabetic rat suggesting the possible beneficial itsrole in the obesity. We aimed to investigate the effect of Cinnamon extract in the normalobese subjects. In this preliminary cross-over clinical trial, 24 normal obese subjectswere recruited and divided randomly into two groups i.e. treatment and placebo. Twograms of the cinnamon extract were given twice daily for 56 days in the treatment group.Normal obese subjects given placebo were allocated as the placebo group. After thetreatment, each of the group ran a one month run-in period, then the groups were crossoveredfor the next 56 days. Body mass index (BMI), insulin serum level, cholesterol andtriglyceride plasma levels were measured at the beginning and at the end of the study.No diet restriction nor exercise intervention was given during the study. At the end of thestudy, BMI in the treatment group (58%) were slightly reduced when compared to theplacebo group (33%), however, it was not significantly different (p>0.05). Moreover,significantly reduction in the insulin serum level was observed in 63% subject in thetreatment group compared to 33% subject in the placebo group (p < 0.05). Additionally,there were no significant differences of cholesterol and triglyceride plasma level observedin the both group. In conclusion, cinnamon extract may give beneficial role in the normalobese subjects by suppressing the serum insulin level. Further studies are required toelucidate the specific role of cinnamon in preventing weight gain.